COMMENTS ON THE ARTICLE BY S.P. YATSYK, T.A. KANEVSKAYA, K.S. ABRAMOV, S.M. SHARKOV, D.K. FOMIN «REPRODUCTIVE HEALTH OF CHILDREN AND TEENAGERS UNDERWENT SURGICAL CORRECTION ASSOCIATED WITH ANDROLOGIC PATHOLOGY» - E.V. Uvarova (Union of pediatricians of Russia, 2009)
.